Application of Fibre Composite Materials for Increasing the Productivity of Production Machines - Zuzana Murčinková; Jaromír Murčinko (Archives of Current Research International, 2015)
The paper presents a case study involved in research project. A case study was based on vibrodiagnostics analyses of unwanted vibrations, machine arrangement and usage of composite materials for increasing the productivity. The main requirement was the increase of productivity of flexographic machine keeping the quality of printing. The paper describes the monitoring, evaluating, comparing machine dynamic response, improving the accuracy of mounting, accuracy of individual machine parts in component joints and modal properties of components made from non-conventional materials to achieve the decrease of vibrations and the increase the damping of flexographic printing machine.